A Study on Industrial Usage of Sugarcane in Different States of India - D. Pandiarajan, Deepak R Kasai (International Journal of Modern Agriculture, 2021)
Sugarcane includes many species of perennial grass, Sugarcane is cultivated in various parts of the country, and every state has specific demand of Sugarcane and according to that specific demand a particular state demands for relatively much greater quantity of Sugarcane for that specific industrial use. But which state demands for more Sugarcane for a specific industrial demand in India is a matter of research. By studying the relative demand of sugarcane for industrial production of specific products, it will become more convenient to improve the crop yield according to the industrial demand in that state. Thus, current research puts light on finding the demand of Sugarcane for various purpose in state of Uttar Pradesh, Gujarat, Maharashtra, and Tamil Nadu and opens the future perspective to conduct more research on the connection of different varieties of cereals and pulses and average consumption of that specific variety in a particular state